2021
DOI: 10.7554/elife.60779
|View full text |Cite
|
Sign up to set email alerts
|

Parabrachial opioidergic projections to preoptic hypothalamus mediate behavioral and physiological thermal defenses

Abstract: Maintaining stable body temperature through environmental thermal stressors requires detection of temperature changes, relay of information, and coordination of physiological and behavioral responses. Studies have implicated areas in the preoptic area of the hypothalamus (POA) and the parabrachial nucleus (PBN) as nodes in the thermosensory neural circuitry and indicate that the opioid system within the POA is vital in regulating body temperature. In the present study we identify neurons projecting to the POA … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 70 publications
3
48
1
1
Order By: Relevance
“…In contrast, a broadly exteroceptive theme may befit the Atoh1 macropopulation. Its neurons overlap axon terminal fields that deliver input from the spinal cord and spinal trigeminal nucleus (Roome et al 2020; Bernard et al., 1995; Blomqvist et al., 1989; Cechetto et al., 1985; Feil & Herbert, 1995; Kitamura et al., 1993; Panneton & Burton, 1985), and it includes subpopulations that relay pain, temperature, and likely also itch information to the forebrain (Barik et al., 2021; Bester et al., 1995; Bourgeais et al., 2001; Deng et al., 2020; Geerling et al., 2016; Mu et al., 2017; Nakamura & Morrison, 2008, 2010; Norris et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a broadly exteroceptive theme may befit the Atoh1 macropopulation. Its neurons overlap axon terminal fields that deliver input from the spinal cord and spinal trigeminal nucleus (Roome et al 2020; Bernard et al., 1995; Blomqvist et al., 1989; Cechetto et al., 1985; Feil & Herbert, 1995; Kitamura et al., 1993; Panneton & Burton, 1985), and it includes subpopulations that relay pain, temperature, and likely also itch information to the forebrain (Barik et al., 2021; Bester et al., 1995; Bourgeais et al., 2001; Deng et al., 2020; Geerling et al., 2016; Mu et al., 2017; Nakamura & Morrison, 2008, 2010; Norris et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Most injection sites and implants were larger than most PB subpopulations, which intermingle extensively, so these approaches simultaneously targeted subsets of PB neurons with distinct connections and functions. Now, genetic methods allow investigators to target more specific subpopulations, including an overlapping potpourri of neurons that express Satb2, Calca , Pdyn, Cck , Oxtr1 , Htr2c , Oprm1 , or Tacr1 (Barik et al., 2021; Chiang et al., 2020; Fu et al., 2019; Garfield et al., 2014; Jarvie et al., 2021; Kaur et al., 2017; Liu et al., 2021; Norris et al., 2021; Palmiter, 2018; Park et al., 2020; Ryan et al., 2017; Yang et al., 2020). Limiting the immense potential of this approach were the lack of a framework for understanding ontological relationships between subpopulations and a lack of markers for remaining PB neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, the authors reported that optogenetic activation of Slc17a6 + (VGLUT2 + ) lPAG neurons increased withdrawal latency in the tail immersion test. In another study, photostimulation of Pdyn + /Penk + /Slc17a6 + lPB neurons that project to the hypothalamus preoptic area (POA) could induce hypothermia, aversion, and suppression of locomotion (107). Disentangling effects on movement from those on nociception and pain experience may not be trivial.…”
Section: Parabrachial Nucleusmentioning
confidence: 99%
“…A series of experimental studies have shown the LPBN neurons to have a pivotal role in the thermoregulatory afferent pathway [29][30][31][32][33][34]. The LPBel/c-POA and LPBd-POA pathways, activated by cool and warm feedforward signals from the skin, will initiate heat gain or heat loss mechanisms, respectively, to preserve the appropriate body temperature from a variety of thermal challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, PGE 2 increased the thermosensitivity of anterior hypothalamus neurons with depressed inhibition [26]. Local thermosensitive neurons have been shown to be present in the external lateral subnucleus (el), central subnucleus (c), and dorsal subnucleus (d) of the LPBN [27,28], which are the 3 LPBN subnuclei responsible for transmitting cutaneous thermosensory signals to the POA [29][30][31][32][33][34]. However, it is still necessary to investigate whether PGE 2 modulates these thermosensitive LPBN neurons.…”
Section: Introductionmentioning
confidence: 99%